Perancangan Destination Branding Desa Wisata Bongan melalui Visual Branding dan Digital Marketing - Dwi Novita Cahyaningtyas Permatasari (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Bongan tourism village assistance includes three activities, namely training on creating website, Instagram, Facebook, and YouTube along with contents management, training on creating video in the perspective of MICE development and digitizing tourism products to promote Bongan tourism villages, designing destination branding through Teruni Bali promotional videos in collaboration with Pemuda Batak Bersatu. Bongan Village was designated as a tourist village in 2018 and is currently classified as startup tourism village. The golden triangle attraction in Bongan village is Puseh Luhur Bedha Temple which has the Kebo Iwa site, Grembengan waterfall, and Bali starling breeding. Lack of knowledge and skills of society in carrying out visual promotion activities digitally encourages the implementation of this training. Mentoring activities are carried out with three methods, lecturing, discussions and practices involving lecturers, students as application of Digital Marketing course, village officer, Pokdarwis, society, other partners, namely Pemuda Batak Bersatu and Teruna-Teruni Bali. In 2020, PIB received an award from the Ministry of Tourism and Creative Economy as the Fifth Grade for the best tourist village mentorship in Indonesia. The design of the logo, website, Instagram, Facebook, and Youtube was well established, ten videos have been successfully produced and uploaded to social media.